Before Adam - London, Jack, 1876-1916 (Salt Lake City, UT : Project Gutenberg, 2008)
"Before Adam" by Jack London is a fictional novel written in the early 20th century. The book explores themes of evolution and ancestral memory through the lens of a unique narrator who experiences vivid dreams of a prehistoric existence. The protagonist, referred to as Big-Tooth, recounts his childhood among primitive ancestors, facing fears and adventures that take place in the wild during the Mid-Pleistocene epoch. The opening of the novel introduces us to Big-Tooth, a child who grapples with nightmarish dreams filled with a profound sense of terror and longing for connection. He is different from his peers, as his dreams are populated by beings from a distant past, and he feels a strong disassociation between his waking life and his dream world. Through his memories, we meet other characters, such as his friend Lop-Ear and the ominous figure Red-Eye, whose violent presence contrasts with the camaraderie of the horde. Big-Tooth's narrative delves into his experiences of fear, discovery of nature, and the instinctual behaviors that define his existence, setting the stage for a deeper exploration of the primitive struggles of humanity. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Before_Adam
Release date is 2008-06-29
John Hamm and David Widger
Keywords: Fantasy fiction; Prehistoric peoples -- Fiction; Dreams -- Fiction